Deficiency of Angiotensin Type 1a Receptors in Adipocytes Reduces Differentiation and Promotes Hypertrophy of Adipocytes in Lean Mice - Putnam, Kelly (Endocrine Society, 2012)
Adipocytes express angiotensin receptors, but the direct effects of angiotensin II (AngII) stimulating this cell type are undefined. Adipocytes express angiotensin type 1a receptor (AT1aR) and AT2R, both of which have been implicated in obesity. In this study, we determined the effects of adipocyte AT1aR deficiency on adipocyte differentiation and the development of obesity in mice fed low-fat (LF) or high-fat (HF) diets. Mice expressing Cre recombinase under the control of the aP2 promoter were bred with AT1aR-floxed mice to generate mice with adipocyte AT1aR deficiency (AT1aR(aP2)). AT1aR mRNA abundance was reduced significantly in both white and brown adipose tissue from AT1aR(aP2) mice compared with nontransgenic littermates (AT1aR(fl/fl)). Adipocyte AT1aR deficiency did not influence body weight, glucose tolerance, or blood pressure in mice fed either LF or high-fat diets. However, LF-fed AT1aR(aP2) mice exhibited striking adipocyte hypertrophy even though total fat mass was not different between genotypes. Stromal vascular cells from AT1aR(aP2) mice differentiated to a lesser extent to adipocytes compared with controls. Conversely, incubation of 3T3-L1 adipocytes with AngII increased Oil Red O staining and increased mRNA abundance of peroxisome proliferator-activated receptor γ (PPARγ) via AT1R stimulation. These results suggest that reductions in adipocyte differentiation in LF-fed AT1aR(aP2) mice resulted in increased lipid storage and hypertrophy of remaining adipocytes. These results demonstrate that AngII regulates adipocyte differentiation and morphology through the adipocyte AT1aR in lean mice.